Tacrolimus Impairs Kupffer Cell Capacity to Control Bacteremia: Why Transplant Recipients Are Susceptible to Infection. Issue 5 (30th March 2021) - Deppermann, Carsten; Peiseler, Moritz; Zindel, Joel; Zbytnuik, Lori; Lee, Woo‐Yong; Pasini, Elisa; Baciu, Cristina; Matelski, John; Lee, Yun; Kumar, Deepali; Humar, Atul; Surewaard, Bas; et al.
Abstract : Background and Aims: Kupffer cells (KCs) are the resident intravascular phagocyte population of the liver and critical to the capture and killing of bacteria. Calcineurin/nuclear factor of activated T cells (NFAT) inhibitors (CNIs) such as tacrolimus are used to prevent rejection in solid organ transplant recipients. Although their effect on lymphocytes has been studied extensively, there are limited experimental data about if and how CNIs shape innate immunity, and whether this contributes to the higher rates of infection observed in patients taking CNIs. Approach and Results: Here, we investigated the impact of tacrolimus treatment on innate immunity and, more specifically, on the capability of Kupffer cells (KCs) to fight infections. Retrospective analysis of data of >2, 700 liver transplant recipients showed that taking calcineurin inhibitors such as tacrolimus significantly increased the likelihood of Staphylococcus aureus infection. Using a mouse model of acute methicillin‐resistant S. aureus (MRSA) bacteremia, most bacteria were sequestered in the liver and we found that bacteria were more likely to disseminate and kill the host in tacrolimus‐treated mice. Using imaging, we unveiled the mechanism underlying this observation: the reduced capability of KCs to capture, phagocytose, and destroy bacteria in tacrolimus‐treated animals. Furthermore, in a gene expression analysis of infected KCs, the triggering receptor expressed on myeloid cells 1 (TREM1) pathway was the one with the most significant down‐regulation after tacrolimus treatment. TREM1 inhibition likewise inhibited KC bacteria capture. TREM1 levels on neutrophils as well as the overall neutrophil response after infection were unaffected by tacrolimus treatment. Conclusions: Our results indicate that tacrolimus treatment has a significant impact directly on KCs and on TREM1, thereby compromising their capacity to fend off infections.